Public health ethics: tradition, profession, and values - Gostin, Lawrence O. (Acta Bioethica, 2003)
This article asks the difficult questions- what is public health? and what is public health ethics? The article also recognizes that even though public health and biomedical ethics overlap, they have distinct aspects. The article examines the unique population-based perspective of public health and how it can be distinguished from patientcentered biomedical ethics. Additionally, public health scholars and practitioners often use ethical analyses with other forms of reasoning, particularly law and human rights. The article, therefore, explores the relationship among public health ethics, public health law and human rights. The various meanings of each form of reasoning are discussed, as well as the similarities and differences among them. The article concludes with a proposal for reconciling the inherent tradeoffs between public health and civil liberties. Prior to exercising compulsory powers, public health officials should examine the risk to the public; the likelihood that the intervention will be effective; the opportunity costs; the burdens on human rights and the policy’s fairness.